Synthesis, structure and magnetic properties of tetrakis-μ-carboxylato-bis(dodecylnicotinato)dicopper(II) complexes; crystal and molecular structure of the decyl carboxylate derivative - Rusjan, Marcia (2000)
Dodecylnicotinate bis-adducts of binuclear copper carboxylates, of the general formula Cu2(O2CCn-1H2n-1)4(C5H4NCOOC12H25)2, were synthesized for n = 10, 12, 14, 16, 18 and 20, and their crystal structure, thermal behavior and magnetic properties studied. The molecular structure of the decyl derivative has been determined from single-crystal X-ray diffraction data. The dimer is centrosymmetric with the CuII ions in a square-pyramidal coordination with four O-alkyl O atoms [average d(Cu - O) 1.960 (6) Å] in the basal plane and the nicotine N atom at apical positions [d(Cu - N) 2.183 (3) Å]. The copper ions, 2.615 (1) Å apart, are bridged by four O-alkyl carboxylate groups. Both the n = 20 and n = 18 homologues exhibit lamellar phases, which can be related to the supramolecular arrangement found in the n = 10 derivative. The magnetic behavior of the decyl and octadecyl dimers was studied in the 2-300 K temperature range. They exhibit a strong intramolecular antiferromagnetic interaction (Cu-Cu superexchange coupling constant J = -347 cm-1 for the decyl derivative), which can be attributed to a large overlap of the metal 3d orbitals and the oxygen lone pair orbitals of the linking carboxylate groups.